Aberrant modulation of ribosomal protein S6 phosphorylation confers acquired resistance to MAPK pathway inhibitors in BRAF-mutant melanoma - Gao Ming-zhao; Wang Hong-bin; Chen Xiang-ling; Cao Wen-ting; Fu Li; Li Yun; Quan Hai-tian; Xie Cheng-ying; Lou Li-guang (Acta Pharmacologica Sinica, 2019)
BRAF and MEK inhibitors have shown remarkable clinical efﬁcacy in BRAF-mutant melanoma; however, most patients develop resistance, which limits the clinical beneﬁt of these agents. In this study, we found that the human melanoma cell clones, A375-DR and A375-TR, with acquired resistance to BRAF inhibitor dabrafenib and MEK inhibitor trametinib, were cross resistant to other MAPK pathway inhibitors. In these resistant cells, phosphorylation of ribosomal protein S6 (rpS6) but not phosphorylation of ERK or p90 ribosomal S6 kinase (RSK) were unable to be inhibited by MAPK pathway inhibitors. Notably, knockdown of rpS6 in these cells effectively downregulated G1 phase-related proteins, including RB, cyclin D1, and CDK6, induced cell cycle arrest, and inhibited proliferation, suggesting that aberrant modulation of rpS6 phosphorylation contributed to the acquired resistance. Interestingly, RSK inhibitor had little effect on rpS6 phosphorylation and cell proliferation in resistant cells, whereas P70S6K inhibitor showed stronger inhibitory effects on rpS6 phosphorylation and cell proliferation in resistant cells than in parental cells. Thus regulation of rpS6 phosphorylation, which is predominantly mediated by BRAF/MEK/ERK/RSK signaling in parental cells, was switched to mTOR/P70S6K signaling in resistant cells. Furthermore, mTOR inhibitors alone overcame acquired resistance and rescued the sensitivity of the resistant cells when combined with BRAF/MEK inhibitors. Taken together, our ﬁndings indicate that RSK-independent phosphorylation of rpS6 confers resistance to MAPK pathway inhibitors in BRAF-mutant melanoma, and that mTOR inhibitor-based regimens may provide alternative strategies to overcome this acquired resistance.